1976
DOI: 10.1042/cs0500455
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Potassium in Body Fluids and Total Body Potassium in Healthy and Diabetic Subjects

Abstract: 1. The concentration of potassium in the erythrocytes and the plasma of forty-one normal subjects and twenty-five diabetic patients was measured and the results were used to calculate the total amount of potassium in the erythrocyte mass and the total amount of potassium in the plasma. The total body potassium was measured in a whole-body monitor. 2. In normal subjects a close correlation was found between total erythrocyte potassium and total body potassium and also between total plasma potassium and total bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…Early cross-sectional studies in Type 1 patients revealed reduced exchangeable potassium or total body potassium to 70 -95% of normal level, suggesting a reduced LBM in patients with longer duration of diabetes [2][3][4][5]. However, recent studies have in accordance with the present results demonstrated similar or even increased LBM in patients with long-term Type 1 diabetes compared with control subjects [8][9][10][11].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Early cross-sectional studies in Type 1 patients revealed reduced exchangeable potassium or total body potassium to 70 -95% of normal level, suggesting a reduced LBM in patients with longer duration of diabetes [2][3][4][5]. However, recent studies have in accordance with the present results demonstrated similar or even increased LBM in patients with long-term Type 1 diabetes compared with control subjects [8][9][10][11].…”
Section: Discussionsupporting
confidence: 83%
“…Since then Type 1 diabetes has been considered as a potentially protein catabolic disease, and it has been taken as scientific fact that loss of weight represents loss of protein in these patients. Several cross‐sectional studies carried out between 1950 and 1975 have confirmed this assumption by demonstrating a reduction in exchangeable potassium or total body potassium in Type 1 patients, indicating a reduction primarily of the fat‐free mass [2–7]. However, four recent studies on body composition in Type 1 patients disagree with this view and have reported that fat‐free mass, the compartment in which protein is contained, is normal or perhaps even slightly increased compared with normal subjects [8–11].…”
Section: Introductionmentioning
confidence: 99%
“…This finding conforms with that of Boddy et al (1976), that in normal subjects red cell potassium values are not related to TBK values and our finding of normal serum potassium values even where TBK is severely depleted reinforces those of other workers (Schloerb et al, 1970).…”
Section: Discussionsupporting
confidence: 94%
“…We found that the patients with hypokalemia had significantly lower LBM levels than those without hypokalemia and that serum potassium levels correlated significantly with LBM levels (r=0.31, p=0.01). The total amount of potassium in the plasma did correlate with total body potassium in normal subjects21), and was expected to bear close relationship to plasma potassium especially when maintained for sufficient time at steady levels 22). A decrease in total body potassium could either reflect a diminishing cellular mass, which is likely to be present in malnutrition, or a change in membrane function that is common in uremia23).…”
Section: Discussionmentioning
confidence: 99%